Orthorexia and vigorexia: Influences of social media on eating patterns and behavior among young adults (Research, Society and Development, 2025)
The aim of this study is to understand how content and interactions on social media influence eating patterns and behaviors among young adults. Orthorexia nervosa is characterized by a pathological obsession with so-called healthy eating, while vigorexia, also known as muscle dysmorphia, is manifested through excessive concern with muscular definition. In contemporary society, digital platforms such as Instagram and TikTok play a central role in shaping habits and aesthetic ideals, while the relentless pursuit of the ideal body and perfect diet has led to the emergence of dysfunctional eating behaviors. Methodologically, this study is an integrative literature review, gathering studies published between 2015 and 2025 from databases such as SciELO, LILACS, Redalyc, Google Scholar, and institutional repositories. The results indicate that frequent use of social media is associated with body image distortion, social comparison, and the development of rigid and perfectionist eating patterns. Methodological limitations still persist—such as the predominance of cross-sectional studies and the lack of culturally validated instruments—highlighting the need for longitudinal research and greater representativeness in the Brazilian context. It is concluded that social media functions as a risk environment for the development and maintenance of emerging eating disorders. For Nutrition practice, recommendations include critical food education, the use of non-moralizing language about food, and careful analysis of digital information sources. Prevention strategies should involve media literacy and interventions aimed at promoting a balanced relationship between eating, body, and technology.